Management of ST-segment elevation myocardial infarction in predominantly rural central China: A retrospective observational study. Issue 49 (December 2016) - Zhang, You; Yang, Shuyan; Liu, Xinyun; Li, Muwei; Zhang, Weidong; Yang, Haiyan; Hu, Dayi; Gao, Chuanyu; Duan, Guangcai
Abstract : Abstract: The degree of adherence to current guidelines for clinical management of ST-segment elevation myocardial infarction (STEMI) is known in developed countries and large Chinese cities, but in predominantly rural areas information is lacking. We assessed the application of early reperfusion therapy for STEMI in secondary and tertiary hospitals in Henan province in central China. Data were retrospectively collected from 5 secondary and 4 tertiary hospitals in Henan concerning STEMI patients treated from January 2011 to January 2012, including management strategy, delay time, and inhospital mortality. Among 1311 STEMI patients, 613 and 698 were treated at secondary and tertiary hospitals, respectively. Overall, 460 (35.1%) patients received early reperfusion therapy including thrombolysis in 383 patients and primary percutaneous coronary intervention in 77. Compared with secondary centers, early (37.2% vs 32.6%) and successful reperfusion (34.5% vs 25.1%) was significantly higher, whereas thrombolysis was lower in the tertiary hospitals (26.4% vs 32.5%). Median symptom onset-to-first medical contact, and door-to-needle and door-to-balloon time was 168, 18, and 60 minutes, respectively. Delay times closely approached recommended guidelines, especially in secondary centers. Use of recommended pharmacotherapy was low, particularly in secondary hospitals. Inhospital mortality was 5.8%, and similar between secondary and tertiary hospitals (6.0% vs 5.6%; P = 0.183). Two-thirds of STEMI patients did not receive early reperfusion, and tertiary hospitals mostly failed to take advantage of around-the-clock primary percutaneous coronary intervention. Actions such as referrals are warranted to shorten prehospital delay, and the concerns of patients and doctors regarding reperfusion risk should be addressed.